Rescuing "emotion labor" from (and for) language teacher emotion research. (April 2023) - Benesch, Sarah; Prior, Matthew T.
Abstract: Recent trends in language education research have brought renewed attention to the significant role of emotions in the experiences and practices of teachers and learners. One concept that has risen to particular prominence is "emotion labor." As originally developed by sociologist Arlie Hochschild (1983), emotion labor refers to tension between specific feelings (and feeling "rules" and displays) that are required and rewarded by one's profession or workplace and one's training and/or beliefs. However, as the term has spread across academia and popular culture, it has increasingly become used in ways that ignore its critical and feminist origins. We perceive this as a loss for language researchers and educators, especially given the reduction in funding for education and increased teacher attrition in response to the global pandemic. Therefore, to cast a light on the recurrent uncritical use of emotion labor and to rescue this concept from (and for) language teacher emotion research, we review research on emotion labor from a poststructural perspective that takes power relations into account. We also seek to disentangle emotion labor from other seemingly resonant concepts such as emotion regulation, emotional intelligence, and emotional literacy. We conclude by proposing an agenda for restoring the critical impetus to emotion labor, especially for researchers and practitioners seeking to better engage with power, agency, social justice, teacher well-being, and educational reforms.